THE 14TH SYMPOSIUM OF THE INTERNATIONAL SOCIETY OF TROPICAL ROOT CROPS – AFRICA BRANCH (ISTRC-AB) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
The International Society for Tropical Root Crops-Africa Branch (ISTRC-AB), symposia serve as a unique platform and a non-profit making professional society for interaction among scientists from around the world working on all tropical root and tuber crops (Sweet-potato, Cassava, Potato, Andean roots and tubers, Yams and Aroids). The Society was created to foster, stimulate, and support any activity leading to the general improvement of the world tropical root and tuber crops production and utilization.